P188 Aboriginal and Torres Strait Australians have significantly worse coronary disease, risk factors and 4 year outcomes compared with non-indigenous Australians. (13th January 2020) - Helms, A; Gilhotra, R; Preston, S; Saireddy, R; Starmer, G; Sutcliffe, S
Abstract: Introduction: The Aboriginal and Torres Strait Islander (ATSI) population in Australia appear to present with coronary disease more frequently, have worse risk factors, worse coronary disease and poorer outcomes, however there is limited data available on this population.  The ATSI population represent 8% of the Cairns total population. We undertook to compare these findings and four-year outcomes in ATSI versus non-indigenous patients aged < 50 years old undergoing coronary angiography. Methods:   We collected data on all patients aged < 50 years old, who underwent coronary angiography at Cairns Hospital over a two-year period (2014-2016), from the Queensland Coronary Outcomes Registry. Data of patient risk factors and 4 year outcomes were collected using electronic hospital medical records and electronic discharge summaries available on all Queensland patients. Patients residing outside Queensland were excluded. Results: From 2014-2016, a total of 555 patients < 50 years old underwent coronary angiography. The average age was 43. 322 (58.0%) patients were male and 233 (42.0%) were female. 271 patients (48.8%) identified as ATSI.  Coronary risk factors - 42.4% of ATSI patients had diabetes vs 13.7 in the non-indigenous group, 58.7% of ATSI patients vs 43.7% had hyperlipidaemia, 61.3% of ATSI patients vs 39.8% were current smokers, 65.3% of ATSI patients vs 42.3% were hypertensive, and 64.2% of ATSI patients vs 50.4% had a family history of premature coronary artery disease. This demonstrates significantly higher incidence of cardiac risk factors in ATSI patients (combined risk factors P = 0.00086).   When comparing coronary artery disease, as demonstrated by coronary angiography, the ATSI group had significantly more abnormal coronary angiograms - 74.5% compared to the non-indigenous group 42.3% (P = 0.000006). There was not a statistically significant difference between the severity of coronary artery disease between the two populations who had coronary disease, however, the ATSI population demonstrated a higher incidence of triple vessel disease. ATSI patients were more likely to have repeat coronary angiography 11% vs 4%. In the four-year follow up period, 18.5% of the ATSI population had at least one major adverse cardiac event (MACE), whereas in the non-indigenous group 7.0% had at least one MACE.  There was not a statistically significant difference between all cause mortality between the two populations. Conclusion:   We have shown that Aboriginal and Torres Strait Islanders Australians are more likely to have coronary angiography at a younger age. That Aboriginal and Torres Strait Islanders Australians have a significantly higher incidence of cardiac risk factors, higher incidence of coronary artery disease, and more major cardiac events after undergoing coronary angiography compared to non-indigenous patients. The all cause mortality in this young population was not significantly different.